Structural and Optical Studies of Ho\(^{3+}\)/yb\(^{3+}\) Co-Doped TiO\(^{2}\) Nanoparticles in Silica Glass - Rai, S. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
The TiO\(_{2}\) nanoparticles doped with Ho\(^{3+}\) and Yb\(^{3+}\) ions were synthesized by sol gel method. The structure of the samples were characterized by XRD, TEM and by thermo gravimetric analysis. The average particle size of the TiO\(_{2}\) range from 7-10 nm (in diameter). The result obtained from TEM, XRD studies indicate that the rare earth ions were positioned in low phonon glass. The photoluminescence (PL) and upconversion (UC) properties of Ho\(^{3+}\) in various concentrations of TiO\(_{2}\) nanoparticles have been investigated. The PL and UC luminescence depends on particle size and crystal structure and we also observed that the emission of Ho\(^{3+}\) in silica xerogel was significantly depends on the amount of TiO\(_{2}\) nanoparticles.